RIE - Pridgeon, Simon (Res Medica, 2014)
The building of the New Royal Infirmary is now under way. How can this smaller hospital meet the demands of its surrounding population? The Royal Infirmary of Edinburgh at Lauriston Place is soon to be replaced by a new 869 bed teaching hospital to be built in Little France, 3 '/2 miles from the city centre. Currently the 1067 bed hospital provides acute care, rehabilitation and long term care as in-patient services as well as a wide range of out-patient facilities. The new RIE will be adopting a new method of care provision and will be organised in a different way to maintain the existing clinical services at the same time as meeting the demands of teaching and research.